PEMBERIAN WARISAN PADA SALAH SATU AHLI WARIS KARENA MERAWAT ORANG TUA PERSPEKTIF TAFSIR HERMENEUTIK AYAT WARIS - Salim, Agus (IAIN Ambon, 2024)
Facts show that some people currently give inherited assets to endow or give to heirs who care for their parents. This is because the heir who takes care of his parents needs it more or finds it more difficult to care for his parents, so that in the view of other heirs, the heir who takes care of his parents is more entitled to receive all the inheritance. Giving inheritance assets to heirs who care for their parents seems to be contrary to the provisions of the Al-Qur'an verse which stipulates that inheritance must be divided according to the provisions in the Al-Qur'an and/or hadith. This research aims to review the interpretation of Al-Qur'an verses regarding inheritance using normative descriptive methodology and a hermeneutic approach as a model of interpretation. It is hoped that this research will be able to contribute to Islamic legal thoughts which continue to experience changes both in the pattern of goals and/or socio-culture, especially the law regarding al-Mu'amalah al-Insaniah Keywords: Distribution of inheritance, heirs who care for parents, Hasan Hanafi’s hermeneutics